Upaya Mengubah Pendapatan Usaha Mikro Kecil Menengah (UMKM) Melalui Digital Marketing - Dini Selasi; Lola Resi Agustiani; Cory Vidiati (PT FORMOSA CENDEKIA GLOBAL, 2022)
Digital marketing has been used in current business activities, including micro, small and medium enterprises (MSMEs). Digital marketing is a transition from conventional marketing to a digital system, this is because consumers are used to looking for needs and shopping online. The research method used is descriptive qualitative with a narrative approach, using primary and secondary data sources, data collection techniques using observation, interviews and documentation with analytical techniques using SWOT analysis. The results of this study show that the community MSMEs in the village have developed well and have been proven to be able to increase the income of the community; The advantages of digital marketing in developing MSMEs are facilitating marketing, saving marketing costs, not recognizing space and time to provide services to consumers, increasing sales as well as maximizing profits.